Introduction to modern cryptography - Katz, Jonathan; Lindell, Yehuda (Boca Raton Chapman & Hall/CRC, 2015)
This book presents the fundamental paradigms of modern cryptography to a general audience with a basic mathematics background. Integrating a practical perspective without sacrificing rigor, this Second Edition offers improved treatment of several topics including stream ciphers, authenticated encryption, hash functions, attacks on poorly implemented cryptography, the random-oracle model, elliptic-curve cryptography, standardized encryption, MAC and digital signature schemes.
Keywords: Cryptography